Harnessing multivariate insights coupled with susceptibility indices to reveal morpho-physiological and biochemical traits in heat tolerance of cotton - Tahira Luqman; Manzoor Hussain; Muhammad Kashif Riaz Khan (BMC Plant Biology)
Abstract Cotton is essential for the global textile industry however, climate change, especially extreme temperatures, threatens sustainable cotton production. This research aims to identify breeding strategies to improve heat tolerance and utilize stress-resistant traits in cotton cultivars. This study investigated heat tolerance for 50 cotton genotypes at the seedling stage by examining various traits at three temperatures (32 °C, 45 °C and 48 °C) in a randomized plot experiment. Analysis of variance revealed significant differences among the genotypes for all the studied traits. Morphological traits, including root and shoot length, fresh and dry root, and shoot weights, were adversely affected by heat stress. Chlorophyll contents declined significantly, indicating impaired and compromised photosynthetic efficiency. Biochemical assays underlined the elevated activities of antioxidant enzymes superoxide dismutase (SOD), peroxidase (POD), total free amino acids (TFA), total soluble sugars (TSS), proline content and declined production of total soluble proteins (TSP), which is indicative of oxidative stress. Physiological traits such as photosynthetic rate and cell membrane stability% decreased severely under stress conditions. The first five PCs under control and the first six PCs under stresses depicted eigenvalues > 1 and presented 72.96%, 76.11%, and 77.93% of total cumulative variability under control, T1 and T2, respectively. Cell membrane stability, a potential marker for heat tolerance, showed a strong positive correlation with total soluble sugars (TSS) and root length (RL) under extreme stress. Based on clustering, the genotypes were classified into four groups. Stress susceptibility indices indicated that NIAB-545 and FH-142 are promising genotypes for developing heat tolerance breeding strategies in cotton.